ETHICS AND PR: RESEARCH ON THE ETHICAL ASPECTS OF USING PR FOR COMMERCIAL AND PUBLIC PURPOSES - Алимова Гузалой Алишер кизи (American Journals, 2024)
The article examines the ethical side of PR as a tool for promoting goods and services, as well as forming public opinion. The author explores the basic principles of ethics in PR, such as honesty, transparency, respect for the audience and responsibility for one's actions.Particular attention is paid to the analysis of examples of ethical problems arising when using PR in various contexts, including the manipulation of information, violation of confidentiality and unethical promotion.The author also analyzes the impact of ethical principles on the effectiveness of PR and offers recommendations for observing ethical standards in PR.The study is of interest to specialists in the field of PR, marketing and advertising, as well as to anyone interested in the ethical aspects of communication and promotion.
Keywords: PR, ethics, promotion, commercial goals, public goals, honesty, transparency.